2016
DOI: 10.1099/mic.0.000248
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria cinerea isolates can adhere to human epithelial cells by type IV pilus-independent mechanisms

Abstract: In pathogenic Neisseria species the type IV pili (Tfp) are of primary importance in hostpathogen interactions. Tfp mediate initial bacterial attachment to cell surfaces and formation of microcolonies via pilus-pilus interactions. Based on genome analysis, many non-pathogenic Neisseria species are predicted to express Tfp, but aside from studies on Neisseria elongata, relatively little is known about the formation and function of pili in these organisms. Here, we have analysed pilin expression and the role of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 88 publications
1
25
0
Order By: Relevance
“…pCONJ1 was linearised by Spe I digestion (New England Biolabs) and a Pme I restriction site added with primers pGL185/pGL186, yielding pCONJ2. Subsequently, the backbone of pCONJ2 was amplified with pGL154/pGL97 and assembled with sfGFP (Pedelacq et al , ) amplified with primers pGL98/pGL155 from pNCC1 sfGFP (Wormann et al , ), generating pCONJ3. pCONJ3 was then linearised by Eco RV digestion (New England Biolabs) and assembled with sacB amplified from pKNG101 using pGL247/pGL248, giving rise to pCONJ4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…pCONJ1 was linearised by Spe I digestion (New England Biolabs) and a Pme I restriction site added with primers pGL185/pGL186, yielding pCONJ2. Subsequently, the backbone of pCONJ2 was amplified with pGL154/pGL97 and assembled with sfGFP (Pedelacq et al , ) amplified with primers pGL98/pGL155 from pNCC1 sfGFP (Wormann et al , ), generating pCONJ3. pCONJ3 was then linearised by Eco RV digestion (New England Biolabs) and assembled with sacB amplified from pKNG101 using pGL247/pGL248, giving rise to pCONJ4.…”
Section: Methodsmentioning
confidence: 99%
“…pLAC101 is a low‐copy‐number plasmid for expressing proteins under IPTG induction. pLAC101 contains the pSC101 origin (amplified with pGL1315/pGL1316 from pUA139) (Zaslaver et al , ), the kanamycin resistance gene and lacI with a cloning site amplified from pNCC1 (Wormann et al , ) with primers pGL897/pGL1314 and pGL894/pGL1314, respectively. pLAC101V5‐ hybA /V5‐ hybA P300A were generated by assembling appropriate fragments into Pac I/ Kpn I‐linearised pLAC101.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we determined whether Tfp are required for the formation of honeycomb-like structures observed during N. cinerea adhesion. N. meningitidis Tfp are essential for efficient adhesion [4] and for signalling that leads to cortical plaque formation [29], but N. cinerea Tfp are dispensable for efficient adhesion [28]. Epithelial cells were infected with a Tfp-deficient mutant (346TΔpilE1/2) and labelled with α-CD44 pAbs at 3 hpi.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…We have previously shown that N. cinerea adheres to epithelial cells, forms microcolonies, and closely associates with microvillus-like structures, similar to those observed during meningococcal adhesion. However, unlike the meningococcus N. cinerea does not require Tfp for attachment and their role during N. cinerea colonisation is not known [28].…”
Section: Introductionmentioning
confidence: 99%
“…In the pathogens, housekeeping sigma factor RpoD initiates pilE transcription from the conserved −35 and −10 recognition sequences in the pilE promoter (Fyfe, Carrick, & Davies, ; Meyer, Billyard, Haas, Storzbach, & So, ). In commensals, sigma factor RpoN initiates pilE transcription by binding to a highly conserved motif (GGN 10 GC) located −24 and −12 bases upstream of pilE (Rendón et al., ; Wormann et al., ).…”
Section: Introductionmentioning
confidence: 99%